Early childhood malnutrition trajectory and lung function at preadolescence. Issue 5 (24th April 2021) - Ferdous, Farzana; Raqib, Rubhana; Ahmed, Sultan; Faruque, ASG; Chisti, Mohammod J; Ekström, Eva-Charlotte; Wagatsuma, Yukiko
Abstract: Objective: Chronic undernutrition is a common phenomenon in Bangladesh. However, information is grossly lacking to report the correlation between chronic undernutrition trajectory and lung function in children. The aim of the current study was to understand the association between early-childhood chronic undernutrition trajectory and lung function at preadolescence. Design: The current study is a part of the 9-year follow-up of a large-scale cohort study called the Maternal and Infant Nutrition Interventions in Matlab. Settings: The current study was conducted in Matlab, a sub-district area of Bangladesh that is located 53 km south of the capital, Dhaka. Participants: A total of 517 children participated in lung function measured with a spirometer at the age of 9 years. Weight and height were measured at five intervals from birth till the age of 9 years. Results: Over half of the cohort have experienced a stunting undernutrition phenomenon up to 9 years of age. Children who were persistently or intermittently stunted showed lower forced expiratory volume (ml/s) than normal-stature children ( P < 0·05). Children who exhibited catch-up growth throughout 4·5 years from the stunted group showed similar lung function with normal counterparts, and a better lung function than in children with the same growth velocity or who had faltering growth. In the multivariable models, similar associations were observed in children who experienced catch-up growth than their counterparts after adjusting for covariates. Conclusion: Our data suggest that catch-up growth in height during early childhood is associated with a better lung function at preadolescence.